Analisis Nilai Karakter pada Implementasi Kesenian Tari Zapin Meskom Bengkalis dalam Pembelajaran Seni Budaya dan Prakarya Di SDN 10 Pinggir: Penelitian Kualitatif - ayu agustina; zufriady zufriady; Hendri Marhadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Instilling character values ​​in Arts, Culture and Crafts (SBdP) learning has an important role in shaping students' personalities from an early age. One form of implementation of character values ​​in learning is through traditional arts, such as the Zapin Meskom Bengkalis Dance. This study aims to describe the movements of the Zapin Meskom Bengkalis Dance and the implementation of this dance in SBdP learning at SDN 10 Pinggir and to analyze the character values ​​contained therein. The method used in this study is descriptive qualitative. Data collection techniques are carried out through observation, interviews, and documentation with triangulation techniques as an effort to validate the data. The results of the study showed that the implementation of the Zapin Meskom Dance in SBdP learning at SDN 10 Pinggir was able to instill various character values, including Religious, hardworking, independent, fair, caring, intelligent, tolerant, honest, and loving. These character values ​​emerge through dance practice, interaction during practice, and the interpretation of the philosophy of the Zapin Meskom Dance. Thus, it can be concluded that the Zapin Meskom Bengkalis Dance not only functions as a means of artistic expression, but also has an important role in shaping students' characters through learning in elementary schools.